The Prevalence and Associated Factors of Self-Reported Knee Injuries Among Amateur Players in Saudi Arabia - Ibrahim Eissa J. Alfaifi; Msaad Alzhrani (Healthcare, 2026)
Background/Objectives: Saudi evidence on self-reported knee injuries among amateur sport participants is limited. We estimated lifetime knee injury prevalence and associated factors. Methods: This cross-sectional study used non-probability convenience sampling to recruit amateur players aged 18–60 years without chronic disease. Data were collected in 2022 using an Arabic study questionnaire and the Saudi Arabic Knee Injury and Osteoarthritis Outcome Score. The primary outcome was a broadly defined, self-reported lifetime knee injury history. Associations were estimated using logistic and Firth penalized logistic regression. Results: Of 462 submissions after the eligibility gateway, 273 were eligible and internally consistent. Most participants were male (89.4%), and football was the most frequently reported sport (74.7%). Overall, 155 participants reported a lifetime knee injury (56.8%; 95% CI 50.8–62.5%). In the adjusted model (n = 269), football participation (aOR = 2.60, 95% CI 1.35–5.13; p = 0.004) and older age (aOR per year = 1.04, 95% CI 1.01–1.08; p = 0.023) were associated with higher odds. Estimates for male sex and high exercise intensity were imprecise. Conclusions: More than half of this convenience sample reported a lifetime knee injury. Football was the most consistent correlate. These cross-sectional findings are neither causal nor nationally representative.